ANALYSIS OF FACTORS AFFECTING BANKING LIQUIDITY AND PROFITABILITY: CASE STUDY OF STATE-OWNED BANKS LISTED ON THE INDONESIA STOCK EXCHANGE PERIOD 2017 – 2019 - Octavia, Evi; Aziizah, Asti Amelia Nur; Puteri, Vioriza Kemala; Pamasti, Dwita; Permata, Amanda; Tama, Fatan Wira (CENTRAL ASIA AND THE CAUCASUS, 2022)
Introduction: This study analyze the factors affecting banking liquidity and profitability of state-owned banks listed on the Indonesia Stock Exchange Period 2017-2019Objective of the paper : This study was conducted to determine and test the effect of the variable Return on Asset (ROA), Current Ratio, and Stock Price onLiquidity and Profitability at state-owned commercial banks listed on IDX for the 2017-2019 period.Method: This study uses secondary data using quantitative methods. There are 4 banks that are researched for 3 years on an annual basis from 2017 to 2019. The analysis used is multiple linear regression analysis. The data were processed using the Eviews 9 application by setting a significance level of 0.05 for testing the hypothesis.Findings : This study finds that both Return On Assets (ROA) and Current Ratio (CR) have a significant effect on the stock prices.Conclusion : It shows that the Return On Assets (ROA) has a positive and significant effect on stock prices. On the other hand, Current Ratio (CR) has a negative and significant effect on stock prices.